Estudo translacional do efeito protetor do guaraná (Paullinia cupana) na exposição ao metilmercúrio - Algarve, Thaís Doeler (2018)
Mercury (Hg) is a known environmental pollutant, especially methylmercury (MeHg) that is toxic during the development of the central nervous system, which can lead to neuromotor impairment, depression, insomnia and anxiety. Using the Drosophila melanogaster model, the effect of fruit fly exposure to MeHg was assessed through the occurrence of neuromuscular (NM) and sleep-wake (SW) disorders present in its progeny obtained by parental or preimaginal (before adult) exposure to this toxin. In parental exposure, flies were exposed 24h to MeHg and transferred to lay eggs in normal medium (without treatment). In preimaginal exposure, flies were exposed to MeHg 24h and only the eggs were kept in the medium with treatment. Both protocols reduced fly viability and locomotor performance (LP), although preimaginal exposure showed stronger impacts. Also, the preimaginal exposure disturbed the flies’ circadian cycle (CC), showing a longer sleep duration and lower daily activity. Results corroborate the hypothesis that low MeHg exposure could trigger subclinical symptoms related to a neurotoxicological development effect. Thus, we evaluated whether guarana could show some protective effect on neuro-oxy-inflammation of SH-SY5Y neural cells and on D. melanogaster neurogenic toxicity (NM and SW patterns). From the previous results, the concentration of 9 μM MeHg and guarana (1-20 mg/mL) was chosen with the combination of the two exposure protocols. It was observed that guarana increased the viability and recovery of LP, especially in males, and reestablish a normal CC patterns with the lowest guarana concentration. With cells exposed 72h to MeHg with a high dose of MeHg (6 μM) combined with 100 μg/mL guarana, an attenuation of toxicity was observed. With a sub-lethal concentration to evaluate the inflammatory activity of MeHg, the cells were exposed to 3 μM combined and 100 μg/mL guarana. The results showed a release reduction of pro-inflammatory cytokines (IL-1β, IL-6, TNFα and IFNγ) and an increase of IL-10 (anti-inflammatory), yet guarana alone was able to reduce IL-6 and INFα. The results together point to a neuroinflammatory effect of MeHg toxicity, since neuroinflammation may be associated with depression and sleep disorders, found here. Guarana showed an anti-inflammatory effect and improved the locomotor deficit and the SW pattern of D. melonogaster. Based on the knowledge that the Amazonian riverine population is chronically exposed to Hg from fish consumption and that in the municipality of Maués (AM) there is a highly longevity elderly population that usually consumes guarana, we analyzed the potential protective effect of guarana against Hg and the relationship with selenium (Se) in survival, motor neurotoxicity and general health parameters in this population with and without habitual consumption of guarana (> 5 times per week). The results showed an increase in survival in individuals who consume guarana habitually and are exposed to high concentrations of Hg. Furthermore, low concentrations of Hg were associated with an increase in the prevalence of systemic arterial hypertension (SAH), as well as high levels of Se and the Se/Hg ratio. Low levels of Se were associated with higher prevalence of healthy volunteers, as well as low levels of Se/Hg ratio. In addition, low levels of Se/Hg were associated with a higher incidence of cardiovascular diseases. Hg levels were positively related to agility test and dynamic balance (TUG's test) and negatively associated measures of limbs and waist circumference. The overall results suggest a protective effect of guarana throughout life stages, since the initial development, seen in in vitro and in vivo results, to a healthier senescence, seen in the elderly population chronically exposed to MeHg. Additional studies are needed for a better understanding on the mechanisms of its toxicity and future therapeutic strategies to protect chronically exposed populations.